Effect of Temperature on Co-Pyrolysis of Palm Kernel Shell and Plastic Waste under Natural Catalysts - Thoharudin, Thoharudin; Nadjib, Muhammad; Ayatullah, Maulana Wahyu (JMPM (Jurnal Material dan Proses Manufaktur), 2024)
Pyrolysis is a potential process for converting solid waste, such as biomass and plastic waste, into useful fuels and chemicals in liquid, solid, and gas forms. The pyrolysis temperature is a critical factor that influences the amount and quality of the product. Furthermore, the use of natural catalysts such as calcium oxide and natural zeolite affects the pyrolysis products. Thus, the purpose of this study is to evaluate the influence of temperature on the amount and quality of pyrolysis products, especially pyrolysis oil, using calcium oxide and natural zeolite catalysts. Pyrolysis was carried out in a stainless steel fixed-bed reactor. The temperature was kept at 400, 450, and 500 oC. The pyrolysis vapor was cooled with a water-jacket condenser, and the oil and wax were collected in an oil chamber. This study found that the pyrolysis temperatures had a substantial impact on the pyrolysis product yields by reducing the char product from 31.25% to 13.9% when the temperature rose in tandem with the fluctuations of other products (wax, liquid, and non-condensable gas). At 450 oC, the liquid product acquired its maximum density, viscosity, heating value, and acidity, which were 906.7 kg/m3, 2.2 cSt, 37.83 MJ/kg, and pH 6.2, respectively. Furthermore, increased temperature promoted the formation of aliphatic hydrocarbons.